A beginner's guide to 3D modeling : a guide to Autodesk Fusion 360 - Coward, Cameron (No Starch Press, Inc., 2019)
"A practical guide to 3D CAD modeling. Begins with the principles of parametric modeling and assembly methods, and then moves on to advanced modeling concepts such as 3D sketching and splines, helixes and ribs, technical drawing, and rendering"--